2010
DOI: 10.4103/0255-0857.71828
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of virulence factors and antibiotic resistance in vancomycin-resistant Enterococcus faecium isolated from sewage and clinical samples in Iran

Abstract: Our results demonstrated that higher number of the clinical E. faecium isolates carried virulence genes than the isolates from STP. Finally, the lack of the genes in clinical and STP isolates confirmed that these genes do not transfer horizontally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 21 publications
2
6
1
Order By: Relevance
“…PCR is a more accurate technique in comparison to the biochemical approach, so PCR results were preferred for the strains with discrepant identification. 22 In this study, the esp gene was detected in 78.3% of E. faecalis and 82% of E. faecium isolates, this finding is similar to the results of other studies, which identified the esp gene in 47.1%, 23 73%, 24 68.4% 7 of E. faecalis , and 80%, 25 26 65%, 27 66%, 23 71%, 24 75% 12 of E. faecium strains. However, this is in contrast to the findings of Shankar et al 28 and Channaiah et al 29 that reported the absence of esp in E. faecium .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…PCR is a more accurate technique in comparison to the biochemical approach, so PCR results were preferred for the strains with discrepant identification. 22 In this study, the esp gene was detected in 78.3% of E. faecalis and 82% of E. faecium isolates, this finding is similar to the results of other studies, which identified the esp gene in 47.1%, 23 73%, 24 68.4% 7 of E. faecalis , and 80%, 25 26 65%, 27 66%, 23 71%, 24 75% 12 of E. faecium strains. However, this is in contrast to the findings of Shankar et al 28 and Channaiah et al 29 that reported the absence of esp in E. faecium .…”
Section: Discussionsupporting
confidence: 91%
“…In some studies, asa 1 was not found in E. faecium but in contrast, in some studies this gene was detected in lower frequency and in our study and some other studies this gene was identified in higher prevalence among E. faecium isolates (Comerlato et al 38 and Kowalska-Krochmal et al 39 ), were detected it among 5%, 65% of VRE fm and 2.7%, 60% of VRE fs strains, respectively. Jahangiri et al 12 were not found asa 1 gene in either 49 of VRE fm strains or 17 of VSE fm strains. Sharifi et al 13 were detected asa 1 gene in 80% of VRE fs and 7.89% of VRE fm strains.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…In a study with the aim to determine the difference in virulence factors expressed by VRE and VSE, it was clearly found that factors like hemolysin production and biofilm formation were more in VSE than VRE isolates, though the difference was not statistically significant [ 6 ]. Similarly, in another study, it was observed that presence of hyl gene, along with simultaneous presence of hyl and esp genes and bacterial adhesion to Vero cells, was more in VSE than VRE isolates, both from clinical and environmental sources [ 32 ]. In a pilot study on enterococcal UTI from the same centre, VRE isolates possessed significantly fewer virulence factors than the susceptible isolates [ 33 ].…”
Section: Discussionmentioning
confidence: 94%